Hypoxia and glucose independently regulate the beta-adrenergic receptor-adenylate cyclase system in cardiac myocytes. - Rocha-Singh, K J (1991)
We explored the effects of two components of ischemia, hypoxia and glucose deprivation, on the beta-adrenergic receptor (beta AR)-adenylate cyclase system in a model of hypoxic injury in cultured neonatal rat ventricular myocytes. After 2 h of hypoxia in the presence of 5 mM glucose, cell surface beta AR density (3H-CGP-12177) decreased from 54.8 +/- 8.4 to 39 +/- 6.3 (SE) fmol/mg protein (n = 10, P less than 0.025), while cytosolic beta AR density (125I-iodocyanopindolol [ICYP]) increased by 74% (n = 5, P less than 0.05). Upon reexposure to oxygen cell surface beta AR density returned toward control levels. Cells exposed to hypoxia and reoxygenation without glucose exhibited similar alterations in beta AR density. In hypoxic cells incubated with 5 mM glucose, the addition of 1 microM (-)-norepinephrine (NE) increased cAMP generation from 29.3 +/- 10.6 to 54.2 +/- 16.1 pmol/35 mm plate (n = 5, P less than 0.025); upon reoxygenation cAMP levels remained elevated above control (n = 5, P less than 0.05). In contrast, NE-stimulated cAMP content in glucose-deprived hypoxic myocytes fell by 31% (n = 5, P less than 0.05) and did not return to control levels with reoxygenation. beta AR-agonist affinity assessed by (-)-isoproterenol displacement curves was unaltered after 2 h of hypoxia irrespective of glucose content. Addition of forskolin (100 microM) to glucose-supplemented hypoxic cells increased cAMP generation by 60% (n = 5; P less than 0.05), but in the absence of glucose this effect was not seen. In cells incubated in glucose-containing medium, the decline in intracellular ATP levels was attenuated after 2 h of hypoxia (21 vs. 40%, P less than 0.05). Similarly, glucose supplementation prevented LDH release in hypoxic myocytes. We conclude that (a) oxygen and glucose independently regulate beta AR density and agonist-stimulated cAMP accumulation; (b) hypoxia has no effect on beta AR-agonist or antagonist affinity; (c) 5 mM glucose attenuates the rate of decline in cellular ATP levels during both hypoxia and reoxygenation; and (d) glucose prevents hypoxia-induced LDH release, a marker of cell injury.